Church Participation in Building Political Civilization in Indonesia - Gilbert Lumoindong; Greivance Lumoindong (CV. Publikasi Indonesia, 2024)
Politics has always been a topic of great interest, especially regarding the church's role. The church is pivotal in advocating for political life aligned with its essence: achieving the common good and public welfare. However, many Christians view politics negatively, often leading to apolitical attitudes. This research aims to analyze the church's participation in reshaping political perceptions among Christians in Indonesia, emphasizing a revolution of love. Using a qualitative method with descriptive and interpretative approaches, the study records congregation perceptions and provides theological interpretations to clarify the connection between politics and the church's role. The results highlight a lack of political education within the church, contributing to Christians' minimal involvement in political arenas. The research underscores the need for the church to educate and equip its congregation for meaningful political participation, fostering integrity and social justice. The study concludes that the church has a crucial role in nurturing a political environment grounded in love, justice, and communal welfare.